Effects of Liraglutide Combined with Short-Term Continuous Subcutaneous Insulin Infusion on Glycemic Control and Beta Cell Function in Patients with Newly Diagnosed Type 2 Diabetes Mellitus: A Pilot Study. (10th November 2015) - Ke, Weijian; Liu, Liehua; Liu, Juan; Chen, Ailing; Deng, Wanping; Zhang, Pengyuan; Cao, Xiaopei; Liao, Zhihong; Xiao, Haipeng; Liu, Jianbin; Li, Yanbing
Abstract : The objective of this paper is to investigate the effects of liraglutide in combination with short-term continuous subcutaneous insulin infusion (CSII) therapy on glycemic control and beta cell function in patients with newly diagnosed type 2 diabetes mellitus (T2DM). Thirty-nine eligible newly diagnosed T2DM patients were recruited and randomized to receive either of two therapies: short-term CSII alone (CSII alone group) or CSII in combination with liraglutide (CSII + Lira group) for 12 weeks. Blood glucose control, homeostasis model assessment (HOMA) indices, and acute insulin response (AIR) were compared between the two groups. The patients in CSII + Lira group achieved euglycemia with equivalent insulin dosage in shorter time (1 (0) versus 2 (3) days, P = 0.039 ). HbA1c at the end of study was comparable between two groups (6.3 ± 0.7 % versus6.0 ± 0.5 %, for CSII alone group and CSII + Lira group, resp., P = 0.325 ). The increment of AIR was higher in CSII + Lira group (177.58 (351.57)  μ U·min/mL versus 58.15 (51.30)  μ U·min/mL, P < 0.001 ). However, after stopping liraglutide, its effect on beta cell function disappeared completely. Liraglutide combined with short-term CSII was effective in further improving beta cell function, but the beneficial effects did not sustain after suspension of the therapy.